The frequency of lymph node metastasis in early-stage adenocarcinoma of the esophagus with incipient submucosal invasion (pT1b sm1) depending on histological risk patterns - Manner, Hendrik; Lorenz, Dietmar (Surgical endoscopy and other interventional techniques, 2015)
Background: A prerequisite for endoscopic treatment (ET) of not only mucosal, but also submucosal early adenocarcinoma of the esophagus (EAC) would be a rate of lymph node (LN) metastasis below the mortality rate of esophagectomy (2-5 %). The aim of the present study was to evaluate the rate of LN metastasis in patients with pT1b sm1 EAC. Methods: 1996-2010, 1,718 patients with suspicion of EAC were referred to the Department of Internal Medicine II at HSK Wiesbaden. In 123/1718 patients, the suspicion (endoscopic ultrasound, EUS) or definitive diagnosis of sm1 EAC (ER/surgery) was made. Rate of LN metastasis was analyzed separately for low-risk (LR; G1-2, L0, V0) and high-risk lesions (HR; G3, L1, V1; ≥ 1 risk factor). LN metastasis was only evaluated in patients who had a proven maximum invasion depth of sm1 (ER and/or surgery), and who in case of ET had a follow-up (FU) by EUS of at least 24 months. Results: Of the 72/123 patients included into the study, 49 patients had LR (68 %) and 23 HR lesions (32 %). In endoscopically treated LR patients (37/49), mean EUS-FU was 60 ± 30 mo (range 25-146); in HR patients undergoing ET (6/23), it was 63 ± 17 mo (46-86; p = 0.4). Mean number of resected LN was 27 ± 16 (12-62) in operated LR patients and 27 ± 10 (12-47) in HR-patients. The rate of LN metastasis was 2 % in the LR (1 patient) and 9 % in the HR group (2 patients; p = 0.24). Mortality of esophagectomy was 3 %. Conclusions: The rate of LN metastasis in pT1b sm1 early adenocarcinoma with histological LR pattern was lower than the mortality rate of esophagectomy. ER may therefore be used alternatively to surgery in this group of patients.
Published 08 October 2014
Gesehen am 17.12.2018
Published online: 8 October 2014